Exploring the Impact of Computer-Based Hybrid Dynamic Assessment on EFL Students' Academic Writing Development - Dayat, Dayat; Mustiah, Mustiah; Meliasari, Rahayu (Journal of Languages and Language Teaching, 2025)
Little attention has been paid to the computer-based hybrid dynamic assessment (C-HDA) in the context of English as a foreign language (EFL) academic writing. However, This study aimed to examine the impact of C-HDA in improving the writing skills of Indonesian higher education students. A sequential explanatory mixed-methods design was employed. To gather quantitative data, one-group pretest-posttest research design was employed. Qualitatively, semi-structured interviews with the experimental group were also conducted to investigate the extent to of mediation benefited the participants during the teaching session. The interview was conducted after the post-test was completed accordingly. Eleven of twenty-two aged 19-20 years old enrolled in the Writing for Academic Purposes course and participated in this research project. The participants were required to write an argumentative essay of 150-300 words consisting of three paragraphs (introduction, body, and conclusion) and their essays were then assessed by using the recent C-HDA. All essays were, then, scored (by three raters) based on five criteria of academic writing, content, organization, language use, mechanics, and style. T-test and the thematic analysis were used to analyze the quantitative and qualitative data, respectively. The results showed that the the current C-HDA improved the participants' academic writing although no maximal score was achieved. In addition, the qualitative data found three themes, positive and negative perspectives, and suggestions that addressed the participants' perceptions toward the C-HDA. This study yields implications for academic writing teachers about the implementation of C-HDA in developing academic writing for low-competent students.